Public Transparency - UNCTAD (World Bank, Washington, DC, 2018)
This note provides guidance on the type of information about agricultural investments that investors and governments can make publicly available. Transparency about certain aspects of investments can improve relations between investors and communities, enable external stakeholders to hold investors to commitments, and improve investors’ public image. Although some information should be kept private to protect commercial interests, in general the amount of publicly available information is insufficient for transparent, accountable conduct of agricultural investments. This has often led to fear, mistrust, and resentment, and created operational and financial difficulties for investors. Some investors and governments have recently shifted toward a more transparent approach, but the risk of misuse of information needs to be managed.